Zolpidem for Catatonia Refractory to Benzodiazepines in Resource-Limited Settings - Holly Hodge; Shaikh Ullahansari; Blake Berry (BJPsych Open)
Aims: Catatonia is a neuropsychiatric syndrome characterized by a paucity of movement and speech. Benzodiazepines are the mainstay of treatment for catatonia, but a subset of patients do not respond. While electroconvulsive therapy is another treatment option for catatonia, access can be limited. This case report discusses the use of zolpidem, a hypnotic non-benzodiazepine GABA-A receptor modulator, in a patient with benzodiazepine-resistant catatonia.